Comparison of simple soil-solution extraction techniques for assessing transfer of metals from soil to plant in contaminated soils - GOLUI, D; DATTA, S P; DWIVEDI, B S; MEENA, M C (The Indian Journal of Agricultural Sciences, 2018)
An attempt was made to evaluate simple techniques for extraction of soil solution for predicting uptake of Zn, Cu, Ni, Pb and Cd by spinach (Beta vulgaris L. var. All Green) grown on metal contaminated soils under modelling framework. Twenty-eight surface soil samples (0-15 cm) with heterogeneous chemical properties were collected. A pot experiment was conducted using spinach as a test crop. The leachate from experimental pots was collected with the help of plastic container installed below the pots. The 1:2 and 1:5 soil: water ratio was used for soil solutionextraction. The total concentration of Zn, Cu, Ni, Pb, and Cd in soil solution was determined using ICP-MS. Harvested plant sample was analyzed for total Zn, Cu, Ni, Pb, and Cd using ICP-MS. For predicting metal uptake by spinach free ion activity model (FIAM) was used and total metal concentration in soil solution was used as an input of FIAM. Higher concentration of all metal in 1:5 soil-water ratio were recorded than that in 1:2 soil-water ratio. The free ion activity model as a function of total metal concentration in soil solution, as measured by 1:5 soil: water extraction, could explain the variability in metal content in spinach to the extent of 94% for Zn, 67% for Cu, 80% for Ni, 50% for Pb and 75% for Cd, respectively. Extraction of soil with 1:5 soil-water ratio is more efficient and suitable for predicting metal uptake by spinach as compared to that of 1:2 and leachate extraction.